CAREC road safety engineering manual 3 roadside hazard management. (CAREC Road Safety Engineering Manuals, 2018)
Single vehicle run-off road crashes are a significant problem on CAREC roads. They are particularly severe and can occur anywhere and at any time. Identifying, investigating, and treating roadside hazards are significant road safety challenges along CAREC highways. It uses a roadside hazard management strategy and the clear zone concept to explain how CAREC road authorities can (i) identify roadside hazards, (ii) investigate how best to treat those roadside hazards, and (iii) implement effective safety improvements. The manual explains the three groups of safety barriers and offers options for safer roadside furniture.